AB0146 DRUG DEPENDENT ALTERATIONS IN B-CELL REPERTOIRE IN SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTS WITH LOW DISEASE ACTIVITY. (2nd June 2020) - Zenz, S.; Dreo, B.; Prietl, B.; Kofler, S.; Sourij, H.; Lackner, A.; D'orazio, M.; Brickmann, K.; Gretler, J.; Fürst-Moazedi, F.; Stradner, M.; Graninger, W.; et al.
Abstract : Background: B-cells play a major role in the pathogenesis and perpetuation of the immune response in systemic lupus erythematosus (SLE). So far, B-cell subtypes have been studied well, but the precise mechanisms of the B-cell alterations during disease activity and during remission, depending on different medication, are still unclear. Objectives: The aim of our study was to investigate the drug dependent alterations in the B-cell repertoire of SLE patients with low disease activity (SLEDAI – 2K ≤4). Methods: Peripheral blood samples from 39 patients suffering from SLE (mean±SD; age 43±13 years, 87.2% females, disease duration 11.1±7 years) were drawn over 2 years. All SLE patients were in remission or low disease activity (median±SE, SLEDAI of 2.0±1.5). B-cells were characterized using CD19, CD20, CD5, CD27 antibodies and were grouped in naïve (IgD + 27 - ), non-switched memory (IgD +, CD27 + ), memory (IgD -, CD27 + ), B1 (CD5 + 27 - ) and MBL-like (CD5 ++ ) B-cells. A quantitative flow cytometric bead-based assay (QuantiBRITE PE kit from Becton Dickinson) was used for the estimation of CD19 antibodies bound per cell. Further, CD38 and CD86 antibodies were used to characterize the B-cell subsets. All cytometric measurements were performed using a standardized BD LSR Fortessa platform. After 3 years of follow-up, patients' data about disease activity and current medication were obtained. Results: 22 SLE patients were treated with hydroxychloroquine (85.8%) and 19 patients received mycophenolate mofetil (MMF; n=14; 54.6%) or azathioprine (AZA; n= 5; 19.5 %). 5 patients were treated with other DMARDs. Independently of hydroxychloroquine and/or MMF, no significant differences were seen in naïve, non-switched memory, post-switched memory, plasma blasts, B1- or MBL-like B-cells. Patients treated with AZA had significantly lower naïve B-cells (mean±SD, 39.3±6.7vs. 73.1±19.3 %; p = 0.028), but had significantly higher IgD-post switched B-cells (31.2±9.1 vs.12.5 ±9.2 %; p = 0.028, respectively) compared with no AZA-treatment. Interestingly, activated B-cells (5.5±1.5 vs. 1.8±1.1%; p = 0.009) were significantly higher in AZA-treated. After 3 years of follow-up, almost all patients were in remission (median±SE, SLEDAI of 2.0±2.0), except of 3 patients with a SLEDAI of ≥ 6. Interestingly, those patients had at baseline, statistically higher naïve B-cells (p = 0.041) and lower B1-like B-cells (p =0.020) compared with patients with low disease activity. Conclusion: Our results suggest that independently of hydroxychloroquine and/or MMF treatment, all patients with low disease activity had similar normal B-cell subsets. Interestingly, in the small group of patients who were treated with AZA, a reduced regeneration of B-cells was shown. Patients with higher disease and high naïve B-cells showed an increased disease activity after three years. Acknowledgments: The research was performed in "CBmed" and funded by the Austrian Federal Government within the COMET K1 Centre Program, Land Steiermark and Land Wien. Disclosure of Interests: None declared